1994
DOI: 10.1136/ard.53.5.331
|View full text |Cite
|
Sign up to set email alerts
|

Long term treatment of polymyalgia rheumatica with deflazacort.

Abstract: Deflazacort was administered at a mean starting dose of 21 8 mg/day with a range of 6-60 mg depending on severity of disease. The Results PATIENTSThe mean age of the 40 patients (24 women/ 16 men) was 70 7 years (range 50-91 years). Patients were referred 4-6 months after the onset of PMR on average (range 1-14 months).Twenty seven patients were allowed to continue treatment with NSAIDs at low doses. Of these, 15 received NSAIDs for less than three months and 12 for 9 7 months in average. The dose of NSAIDs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 13 publications
0
13
0
3
Order By: Relevance
“…One study each reported a lower discontinuation rate of GCs after 2 years (n=50, LoB 4/8),14 a longer duration of GC therapy (n=183, LoB 3/8),32 a higher risk of developing GCA (n=176, LoB 5/8)25 and a higher cumulative GC dose (n=80, LoB 4/8) 37. Additionally, GC side effects were generally more common among women than men (three studies, total n=196, LoB 2–4/8) 31 36 37…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study each reported a lower discontinuation rate of GCs after 2 years (n=50, LoB 4/8),14 a longer duration of GC therapy (n=183, LoB 3/8),32 a higher risk of developing GCA (n=176, LoB 5/8)25 and a higher cumulative GC dose (n=80, LoB 4/8) 37. Additionally, GC side effects were generally more common among women than men (three studies, total n=196, LoB 2–4/8) 31 36 37…”
Section: Resultsmentioning
confidence: 99%
“…A single study, for example, showed a higher relapse rate in women than in men,37 whereas eight other studies found no such association 18 20 24 34 41 51 52 57. On the other hand, women appeared to have a longer duration of treatment,14 32 higher cumulative GC doses37 and more GC-related side effects 31 36 37. Whether female patients benefit from a closer (than standard) clinical monitoring, a lower initial GC dose and a lower threshold for using MTX has to be clarified by future clinical studies.…”
Section: Discussionmentioning
confidence: 98%
“…Baseline factors that were associated in low to moderate quality studies with a higher relapse rate and/or prolonged therapy in PMR studies were: female sex (24,26), high ESR (.40 mm/hour) (26)(27)(28)(29)(30)(31) and peripheral inflammatory arthritis (32). A number of equally low to moderate quality studies, however, failed to demonstrate an association between these factors and relapse/prolonged therapy (27)(28)(29)(30)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44). C. Consideration of specialist referral, particularly in case of atypical presentation (such as peripheral inflammatory arthritis, systemic symptoms, low inflammatory markers, age ,60 years), experience of or high risk of therapy-related side effects, PMR refractory to GC therapy, and/or relapses/prolonged therapy.…”
Section: Resultsmentioning
confidence: 99%
“…A too rapid tapering is another common attitude that favours relapses. Italian GPs sometimes use deflazacort, the efficacy of which seems to be similar to that of prednisone (28)(29)(30). However, the benefit of deflazacort in terms of side effects is unclear, it is not reimbursed by the Italian National Health System, and is more expensive than prednisone.…”
Section: Reviewmentioning
confidence: 99%